Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

To evaluate this type of limits, how can I do, considering $f$ differentiable, and $ f (x_0)> 0 $

$$\lim_{x\to x_0} \biggl(\frac{f(x)}{f(x_0)}\biggr)^{\frac{1}{\ln x -\ln x_0 }},\quad\quad x_0>0,$$

$$\lim_{x\to x_0} \frac{x_0^n f(x)-x^n f(x_0)}{x-x_0},\quad\quad n\in\mathbb{N}.$$

share|improve this question
add comment

4 Answers 4

up vote 2 down vote accepted

For the first: for $x\neq x_0$, since $f(x)>0$ in a neighborhood of $x_0$ \begin{align*} \frac{f(x)}{f(x_0)}^{\frac 1{\ln x-\ln x_0}}&=\exp\left(\frac {\ln f(x)-\ln f(x_0)}{\ln x-\ln x_0}\right)\\ &=\exp\left(\frac {\ln f(x)-\ln f(x_0)}{x-x_0}\frac{x-x_0}{\ln x-\ln x_0}\right), \end{align*} and taking the limit $x\to x_0$, since $\ln f$ is differentiable, we get $$\lim_{x\to x_0}\frac{f(x)}{f(x_0)}^{\frac 1{\ln x-\ln x_0}}=\exp\left(\frac{f'(x_0)}{f(x_0)}\frac 1{\frac 1{x_0}}\right)=\exp\left(x_0\frac{f'(x_0)}{f(x_0)}\right).$$ For the second question \begin{align*}\frac{x_0^nf(x)-x^nf(x_0)}{x-x_0}&=x_0^n\frac{f(x)-f(x_0)}{x-x_0}+f(x_0)\frac{x_0^n-x^n}{x-x_0}\\ &=x_0^n\frac{f(x)-f(x_0)}{x-x_0}-f(x_0)\sum_{k=0}^{n-1}x^kx_0^{n-k-1}, \end{align*} and taking the limit $x\to x_0$ we get $$\lim_{x\to x_0}\frac{x_0^nf(x)-x^nf(x_0)}{x-x_0}=x_0^nf'(x_0)-nf(x_0)x_0^{n-1}.$$

share|improve this answer
add comment

Hint: write $x=x_0+h$ with $h\to0$ and expand each term up to order $h$.

For example, $\log(x)-\log(x_0)=\log(1+h/x_0)=h/x_0$ and $f(x)=f(x_0)+hf'(x_0)$ hence $f(x)/f(x_0)=1+hf'(x_0)/f(x_0)$, hence...

share|improve this answer
add comment

For the second limit you can also observe that if $x_0 \neq 0$ then

$$\lim_{x\to x_0} \frac{x_0^n f(x)-x^n f(x_0)}{x-x_0} = \lim_{x \to x_0}x^nx_0^n \frac{ \frac{f(x)}{x^n}- \frac{f(x_0)}{x_0^n}}{x-x_0}= (x_0)^{2n} (\frac{f(x)}{x^n})'(x_0) \,.$$

The case $x_0=0$ is trivial.

share|improve this answer
add comment

For the first problem, one may be tempted to use L'Hopital's Rule:

Noting that $f(x)>0$ for $x$ sufficiently close to $x_0$:

$$\ln \biggl[\,\Bigl ({f(x)\over f(x_0)}\Bigr)^{1\over \ln x-\ln x_0}\,\biggr] = {\ln f(x)-\ln f(x_0)\over \ln x-\ln x_0}.$$

We have: $$\tag{1}\lim_{x\rightarrow x_0} {\ln f(x)-\ln f(x_0)\over \ln x-\ln x_0} = \lim_{x\rightarrow x_0} {{f'(x)/ f(x)} \over 1/x} =\lim_{x\rightarrow x_0} { {xf'(x)\over f(x)} }={ {x_0f'(x_0)\over f(x_0)} }. $$

So $$\lim_{x\rightarrow x_0}\Bigl ({f(x)\over f(x_0)}\Bigr)^{1\over \ln x-\ln x_0}= \exp\Bigl({ {x_0 f'(x_0)\over f(x_0)} }\Bigr). $$

But, this line of reasoning is incorrect. We do not know that the last limit appearing in (1) exists.

See the other answers for correct arguments.

share|improve this answer
Would this be better as a comment? –  David Mitra Dec 31 '11 at 1:20
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.